CYTOLOGICAL STUDIES OF AL STUDIES OF AL STUDIES OF ADHATODA L. SPECIES AND BARLERIA L. SPECIES L. SPECIES - SEEMA SHARMA; DIMPLE SHARMA; R. K. RAGHUVANSHI; R. A. SHARMA; PAYAL CHANDRAWAT (The Bioscan, 2010)
Four selected plants types namely Barleria cristata L., Barleria priontis L., Adhatoda beddomei L. and Adhatoda vasica L. have been studied for chromosome number and chromosomal associations, chiasma frequency, tetrads of microspores and pollen grains. In all the four plant types, the chromosome numbers remain more or less same (2n = 32 or 34). However, there is minute difference in the frequency of univalents in both species of Barleria (B. cristata = 2.8, B. prionitis = 4.4). Both the species of Adhatoda differ from the two species of Barleria in having the linear type of tetrads. Overall tetrads of Adhatoda species are quite smaller than that of Barleria species. Both viable and nonviable pollen grains are larger in Barleria species in comparison to those of Adhatoda species. The pollen viability among the selected four species does not show much variation but the pollen morphology is quite distinct from each other.